(untitled) (Research, Society and Development, 2020)
Schistosomiasis is an asymptomatic disease caused by Schistosoma mansoni (S.mansoni), which can cause serious problems in the host’s organism. In Sergipe, 946 cases had been reported in the last decade. Since the state is in an endemic position regarding the disease, there is a need to carry out an epidemiological characterization of schistosomiasis mansoni cases to carry out an epidemiological characterization of the cases of Schistosoma mansoni in the state of Sergipe, between 2008 and 2017. This study of quantitative approach and descriptive character was based on secondary data available in the Hospital Information System of SUS (SIH / SUS), by the Department of Informatics of the Unified Health System (DATASUS), from 2008 to 2017. After analyzing the available information, there was no significant difference between the affected sexes. The age groups 10 to 14, 40 to 59, and 60 to 79 were statistically equal to individuals aged 20 to 39 years. The brown race was the most affected. The outcome of “death from schistosomiasis” did not show any significant difference concerning to “cure”, it is a warning data for public health. The regions most affected were Itabaiana and Aracaju. There is an urgent need to strengthen and encourage programs to combat this pathology in Sergipe.